Bakti Sosial Berbagi Paket Sembako Dan Buka Puasa Bersama Di Panti Asuhan Uswatun Hasanah Kota Batam - Supardi; Arina Luthfini Lubis; Zaharafatimah; Mohammad Nur Afriliandi Nasution (JURNAL KEKER WISATA, 2023)
We servants carry out Social Service activities because this activity is very beneficial both for students in growing their social spirit and concern, as well as having the benefit of easing the burden on the children sheltered by the orphanage. This activity was carried out in collaboration between students and lecturers so that the event was more focused and on target. This service was carried out by visiting the intended orphanage, namely the Uswatun Hasanah Orphanage which is located in Sagulung District, Batam City. The Uswatun Hasanah Orphanage fulfills the needs of the children it cares for, from food to school. The Batam City orphanage is open to donations from donors and residents. Initially, the economy at this orphanage was sufficient because there were donors who helped. However, when the pandemic came, the aid funds from donors decreased. This is not proportional to the number of children in the orphanage. Social service activities are acts of kindness done for the benefit of others. This social service activity can develop brotherhood between individuals and foster a sense of kinship and kinship. This activity is also in line with PkM's vision of giving back to the community. This activity was held to coincide with the holy month of Ramadan so that it was combined with an iftar together. Through this activity it is hoped that both students, lecturers and orphanage children can take positive values ​​and wisdom from this activity.